Nurses’ Experience of Dealing With Patients’ Aggressive Behaviour in Psychiatric Emergency Ward of Hospital in South Sulawesi - Hasnah Hasnah; Hapsah Hapsah; Silvia Malasari; Ariyanti Saleh; Akbar Harisa (Indonesian Contemporary Nursing Journal, 2018)
Introduction: The high level of risk emergency psychiatry nurse becomes the target of aggressive behavior in patients both physically and psychologically, providing a special experience for nurses. Positive and negative impacts felt more likely a psychological effect on the nurse. Objective: Identifying the experiences of nurses dealing with patient of aggressive behavior in Emergency Psychiatric of Rumah Sakit Khusus Daerah Provinsi Sulawesi Selatan. Methods: The phenomenological approach to decision informants using purposive sampling with the informant as much as 9 informants who have experienced aggressive behavior from patients. Results: There were 7 themes obtained by the feelings of nurses with aggressive behavior patients, nurses experienced different kinds of aggressive behavior,  nurses identified about the causes of the patient's aggressive behavior, nurse found some signs of the patient while being aggressive, nurses perceived impact of agresive behavior after getting the incident of it, the way nurses treated patients aggressive behavior, and nurses found obstacle to overcome aggressive behavior's patient. The positive experience of nurses in dealing with patient of aggressive behavior was nurse know the proper ways, causes and signs of the patient while being aggressive so the nurse was able to anticipate the action will be carried out. On the other hand the negative experience felt by the nurse due to the impacts of the aggressive behavior patients. Conclusions and:  The experience felt by nurses in dealing with patients in Psychiatric Emergency Unit of Rumah Sakit Khusus Daerah Provinsi Sulawesi Selatan there were positive and negative. Therefore, we need a way to reduce aggressive behavior and provide management training for nurses in dealing with aggressive behavior in order to keep patients safely.